The mediating role of anxiety to perform social skills between parental attachment and adolescents' self-efficacy - Parsa, Nakisa; Redzuan, Ma'rof; Yaacob, Siti Nor; Parsa, Parisa; Parsa, Bita (Marsland Press, 2014)
The present study examined the mediating role of adolescent’s anxiety to perform social skills on the relationships between perceived parental attachment and self-efficacy among 374 Iranian adolescents aged 17 to 19 years old. Survey results showed that parental attachment was significantly related to an adolescent’s self-efficacy (p<0.05). Moreover, the results revealed that adolescents with low self-efficacy experienced higher anxiety to perform social skills (p<0.05). Anxiety to perform social skills mediated the relationship between parental attachment and adolescents’ self-efficacy (p<0.05). The findings highlighted the mediating role of anxiety to perform social skills on the relationship between parental attachment and adolescent’s self-efficacy.